Relationships between Bone Turnover and Energy Metabolism - Tânia A. P. Fernandes; Luísa M. L. Gonçalves; José A. A. Brito (Journal of Diabetes Research)
It is well established that diabetes can be detrimental to bone health, and its chronic complications have been associated with an increased risk of osteoporotic fracture. However, there is growing evidence that the skeleton plays a key role in a whole-organism approach to physiology. The hypothesis that bone may be involved in the regulation of physiological functions, such as insulin sensitivity and energy metabolism, has been suggested. Given the roles of insulin, adipokines, and osteocalcin in these pathways, the need for a more integrative conceptual approach to physiology is emphasized. Recent findings suggest that bone plays an important role in regulating intermediary metabolism, being possibly both a target of diabetic complications and a potential pathophysiologic factor in the disease itself. Understanding the relationships between bone turnover and glucose metabolism is important in order to develop treatments that might reestablish energy metabolism and bone health. This review describes new insights relating bone turnover and energy metabolism that have been reported in the literature.